Cutting Edge Research in the Contact Zone? The Establishment of the Nutritional Research Laboratories in Coonoor (1925–27). Issue 1 (2nd January 2021) - Malhotra, Ashok
Abstract: By 1928, Robert McCarrison's laboratories in the South Indian hill station of Coonoor had become recognised as the centre for nutritional research in India. Five years earlier, however, his institute had faced closure. This article argues that the establishment of McCarrison's institute was based on his pitch to the Royal Commission on Agriculture in India in 1926, in which he successfully aligned his research to satisfy the concerns of various members of the Commission. This discussion uses McCarrison's lobbying for his institute as a case study to examine the broader political manoeuvrings that colonial scientists in the early twentieth century often had to undertake to establish their research agendas.